## Trending News

Promoted

# If one of the roots of the equation x² - Kx+27=0 is the square root of the other, find the other root and hence the value of K.?

### 4 Answers

Relevance

- khalilLv 72 years agoFavorite Answer
ax² + bx + c = 0

the roots ... m ....√m

the product of the roots = c/a

m*√m = 27

m^3/2 = 27

m = 9 and m' = 3

the sum of the roots = -b/a

9 + 3 = k

k = 12

- ?Lv 72 years ago
If one of the roots of the equation x² - Kx + 27 = 0 is the square root of the other,

find the other root and hence the value of K.

K = 12

x² - Kx + 27 = x² - 12x + 27 = (x - 3)(x - 9)

- lenpol7Lv 72 years ago
Factor

( x - 9)(x - 3) = 0

x = 9

&

x = 3

'3' is the square root of '9'

x^2 - 9x - 3x + 27 = 0

x^2 - 12x + 27 = 0

Hence K = 12

Still have questions? Get your answers by asking now.